Effect of pharmacokinetic/pharmacodynamic ratio on tigecycline clinical response and toxicity in critically ill patients with multidrug-resistant Gram-negative infections. (September 2020) - Ruiz, Jesus; Ramirez, Paula; Villarreal, Esther; Gordon, Mónica; Sánchez, María Ángeles; Martín, María; Castellanos-Ortega, Álvaro
Introduction: The information about the pharmacokinetics and optimal dose of tigecycline in critically ill patients with severe underlying diseases is limited and controversial. In this study, we evaluate the pharmacokinetic parameters of tigecycline in critically ill patients with multidrug-resistant Gram-negative infection and explore the association between the pharmacokinetic/pharmacodynamic ratio and treatment response. Methods: A prospective study was designed including critically ill patients treated with tigecycline for multidrug-resistant Gram-negative infections. Blood samples were collected at day 3–5 of treatment, and pharmacokinetics parameters were evaluated using NONMEM ® software. Relationship between area under the free concentration–time curve and minimum inhibitory concentration ratio (fAUC/MIC) and treatment failure was evaluated. Association between tigecycline fAUC and hepatobiliary toxicity was also investigated. Results: Twenty-five critically ill patients were included in the study. In the pharmacokinetic model, weight and total bilirubin level were found to be significant predictors of tigecycline clearance. Fifteen (60.0%) patients achieved an fAUC/MIC ratio >4.5, seven (28.0%) an fAUC/MIC > 6.96 and only three (12.0%) an fAUC/MIC > 17.9. No differences in fAUC/MIC ratio were obtained between those patients with and without clinical failure (5.28 (IC95%: 2.57–7.94) vs 8.71 (3.57–13.84)). fAUC values were higher in those patients who suffered hepatobiliary disorders (7.63 (3.93–11.34) vs 17.63 (7.85–26.28) mg/L/h). Conclusion: An important percentage of critically ill patients with multidrug-resistant Gram-negative infection treated with tigecycline do not achieve an appropriate pharmacokinetic/pharmacodynamic value. Tigecycline fAUC seems to be associated with hepatobiliary disorders in this study population. The effect of fAUC/MIC ratio on clinical response remains unclear.